Comparison of transcutaneous electrical tibial nerve stimulation for the treatment of overactive bladder: a multi-arm randomized controlled trial with blinded assessment (Clinics, 2021)
OBJECTIVE: To compare the effectiveness of tibial nerve transcutaneous electrical nerve stimulation (TENS) for an overactive bladder, considering the sites of application and frequency of attendance.METHODS: This multi-arm randomized controlled trial enrolled 137 adult women (61.0±9.0 years) with overactive bladder from a university hospital. They underwent 12 sessions of 30-min TENS application and were assigned to five groups: one leg, once a week (n=26); one leg, twice a week (n=27); two legs, once a week (n=26); two legs, twice a week (n=28); and placebo (n=30). Symptoms of overactive bladder and its impact on quality of life were evaluated before and after 6 or 12 weeks of treatment using the Overactive Bladder Questionnaire-V8 and voiding diary. ClinicalTrials.gov: NCT01912885.RESULTS: The use of one leg, once a week TENS application reduced the frequency of urgency episodes compared with the placebo (1.0±1.6 vs. 1.4±1.9; p=0.046) and frequency of incontinence episodes compared with the placebo (0.7±1.4 vs.1.4±2.2; p<0.0001). The one-leg, twice a week protocol decreased the urinary frequency compared with the two legs, once a week protocol (8.2±3.5 vs. 9.0±5.1; p=0.026) and placebo (8.2±3.5 vs. 7.9±2.7; p=0.02). Nocturia improved using the two legs, once a week protocol (1.5±1.8) when compared with the one leg, twice a week protocol (1.9±2.0) and placebo (1.7±1.6) (p=0.005 and p=0.027, respectively). Nocturia also improved using the two legs, twice a week protocol when compared with the one leg, twice a week protocol (1.3±1.2 vs.1.9±2.0; p=0.011).CONCLUSION: One-leg stimulation improved the daily urinary frequency, urgency, and incontinence, and the two-leg stimulation once and twice weekly improved nocturia.